Methane emissions from municipal landfills: a case study of Chandigarh and economic evaluation for waste-to-energy generation in India - Mor, Suman; Kaur, Kamalpreet; Ravindra, Khaiwal (Frontiers in Sustainable Cities, 2024)
Municipal waste, containing a large proportion of organic matter, is dumped into solid waste disposal sites, which after anaerobic decomposition, releases methane (CH4). Landfill gases such as CH4 contribute significantly to global warming, while they can be used for waste to energy generation. Method: The waste samples were obtained using the quartile method and were examined in the laboratory for proximate and ultimate analysis using standard methodology. The inventory and estimation of CH4 generation were done using International Panel on Climate Change methodology, including the potential of electricity generation from the CH4 generated. Results: The results showed that the city generates around 350 TPD of waste which comprised of Plastic/ Polythene < Clothes < Paper < Wood < Organic/Vegetables < Leaves + hay + straw < Inerts < Rubber/leather < Miscellaneous, in the same order. The estimated amount of municipal waste with observed composition led to the generation of 0.34 Gg/yr of CH4. Conclusions: Depending on the efficiency of the gas energy system, 0.27 MW to 0.77 MW of electric power can be produced in Chandigarh, and that yields a financial gain of approximately 0.15 million USD. The extrapolation of these estimates for the Indian landfill's CH4 utilization offers an energy generation potential of 13 billion USD.